An ethnobotanical study on the wild edible plants used by forest dwellers in Yangoupokpi Lokchao Wildlife Sanctuary, Manipur, India - Laishram Ricky Meitei; De, Aparajita; Ashiho Asoshii Mao (Ethnobotany Research and Applications, 2022)
Background: The study documented the wild edible plants (WEPs) used by forest dwellers in the Yangoupokpi Lokchao Wildlife Sanctuary (YLWLS), Manipur, India. The inhabitants of YLWLS belong to the Thadou, Meitei, and Maring communities. Methods: An ethnobotanical survey was carried out from March 2018 to February 2020. The elderly local people, local healers, forest staff, and vendors in local markets participated in the survey. The respondents were selected through snowball sampling method. The ethnobotanical information was gathered from the respondents, especially the elderly people, local healers, forest staff, and vendors through interviews. The questionnaire used was a semi-structured type. The data was collected on parameters such as vernacular name, botanical name, family, the life form or habit of the species, information on flowering and fruiting, the plant part used, mode of consumption, medicinal use, marketability, and price. The voucher specimens of the wild edible plants were collected and identified with the help of literature. Results: One hundred and eight taxa belonging to 86 genera and 50 families of WEPs were documented. Zingiberaceae was the most dominant family with seven species used as WEPs. Herbs were most dominant with 42 species. Nine species bore flowers and fruits all year round. Maximum species (49 species) were consumed after cooking. Forty-nine species out of the 108 WEP species were consumed for their medicinal values. Sixty six species (61%) of WEPs were marketed. The highest-priced species were Asparagus racemosus (INR 180-220/kg; USD 2.41-2.95) and Cinnamomum verum (INR 150-200/kg; USD 2.01-2.68). The use of the pseudostem of Ensete glaucum as food is a new report for Manipur. Conclusions: The forest dwellers depend on the WEPs for their food, medicine, traditional ceremonies, and source of livelihood. Some species of WEPs could be propagated for conservation, management, and sustainable utilization, which would help in generating additional income for the locals. Keywords: Wild edible plants, forest dwellers, Yangoupokpi Lokchao Wildlife Sanctuary, Manipur